Environmentally engaged research: An interview with Paul Adam. (17th January 2018) - Adam, Paul; McDonald, Tein
Abstract : For over three decades, New South Wales ecologist Paul Adam has worked to promote the study and conservation of native ecosystems and has served on scores of agency and NGO committees. Here, Paul provides some insight into what motivates such a sustained contribution.